DIGITAL ARCHIVE OF UKRVO: THE POSITIONAL ACCURACY OF MINOR PLANETS DETERMINATIONS - Golovnya, V.; Andruk, V. (Одеські астрономічні публікації, 2013)
Scanning and astrometric processing of two 30x30 cm photographic plates with images of minor planets were conducted. The plates were obtained at the double wide-angle astrograph (DWAA, 400/2000) on the program of photographic sky survey and the program of small planets’ observations. The plates were digitized using a flatbed scanner Epson Expression 10000XL. Images were obtained in the gray range of 16 -bits with a resolution of 1200dpi (> 11,000 pix along the one of the axies) and included into the UkrVO Joint Digital Archive (JDA). The plates are related to GUA040C observational archive. Image processing has been carried out in software package LINuS/MID AS/ROM AFOT. Topocentric equatorial coordinates for the second exposition minor planet images were obtained with a single measurement error ± 0.1 " and ± 0.3" for coordinate and ± 0.2m for magnitudes in the Tycho-2 catalog as reference.